Numerical investigations of new low‐order explicit last stage diagonal implicit Runge–Kutta schemes with the finite‐element method - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Abstract Initial value problems can be solved efficiently by means of Runge–Kutta algorithms with adaptive step size control. Diagonally implicit Runge–Kutta (DIRK) methods are the most popular class among the diverse family of Runge–Kutta algorithms. In this paper, the novel class of low‐order explicit last‐stage diagonally implicit Runge–Kutta (ELDIRK) methods are explored, which combine implicit schemes with an additional explicit evaluation as an explicit last stage. ELDIRK Butcher tableaus are used to control embedded RK methods to obtain solutions of different orders. The lower‐order solution is obtained by classical implicit RK stages and the higher‐order solution is obtained by additional explicit evaluation. As a result, a significant reduction in computational cost is achieved by skipping the iterative solution of nonlinear systems for the additional step. The examination of the heat problem and the use of the innovative Butcher tableau in the finite‐element method are the main contributions of this work. Thus, it is possible to establish adaptive step size control for the new low‐order embedded methods based on an empirical method for error estimation. Two‐dimensional simulations are used to show an appropriate algorithm for the ELDIRK schemes. The new Runge–Kutta schemes' predictions of higher‐order convergence are confirmed, and their successful outcomes are illustrated.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

No effects of different perturbations on the performance in a mental body-rotation task (MBRT) with egocentric perspective transformations and object-based transformations - Budde, Kirsten; Weigelt, Matthias (Human Movement Science)
The present study investigates participants' performance in two different mental body-rotation tasks (MBRTs) under conditions in which dynamic stability is challenged in two different balancing conditions: active balance control (Experiment 1), where participants actively maneuver, and re-active balance control (Experiment 2), where participants react to an external perturbation. The two MBRTs induced either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment). In Experiment 1, 48 participants were tested while standing on an even ground (low balancing requirements) or on a balance board (high balancing requirements). In Experiment 2, 32 participants performed while either standing still on a vibration plate or with the vibration plate moving in a low (20 Hz) or high (180 Hz) frequency. In both experiments, the results for response time and response error revealed effects of rotation angle and type of task. An effect of balancing condition was only observed for response error in Experiment 1. More precisely, response times and response errors increased for higher rotation angles. Also, performance was better for egocentric than for object-based spatial transformations. However, the different challenges to dynamic stability in Experiments 1 and 2 did not influence performance in the two MBRTs (except for response errors in Experiment 1) nor in a control condition (Experiment 1) without mental rotation.
Keywords: Mental rotation; Balance control; Perturbation; Embodiment

Rezension: Erika Thomalla: Anwälte des Autors. Zur Geschichte der Herausgeberschaft im 18. und 19. Jahrhundert, Göttingen: Wallstein 2020 und Ines Barner: Von anderer Hand. Praktiken des Schreibens zwischen Autor und Lektor, Göttingen: Wallstein 2021 - Spener, Anna Maria; Heimgartner, Stephanie (Sprache und Literatur)

Investigation of the Volume Flow in the FFF Process as an Influencing Factor on the Resulting Orientation of Thermally Conductive Filler Particles - Moritzer, Elmar; Elsner, Christian Lennart; Deupmann, K.

Investigation of the influence of screw geometry on the resulting melt quality for cast film extrusion - Schöppner, Volker; Trienens, Dorte

Großflächig, komplex? InMould-Plasma ist die Lösung! - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Rauen, Dennis; Kolbe, B.; Schlee, H.; Hokamp, C. (Kunststoffe)

Goodbye Hot Spots - with No Extra Energy Expenditure - Moritzer, Elmar; Kartelmeyer, Stephan; Kreamer, Dennis; Jaroschek, Christoph (Plastics Insights)

Hauptsache, die Wellenlänge stimmt - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

Hotspots ade - ohne Extra-Energieaufwand - Moritzer, Elmar; Kartelmeyer, Stephan; Kraemer, Dennis; Jaroschek, Christoph (Kunststoffe)

Optimization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian

Optimisation of the Simulation of Rubber Extrusion dies by means of the Integration of empirically determined characteristic Maps - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Wiesel, C.; Nillius, U.; Schön, M.; Limper, A. (KGK Kautschuk Gummi Kunststoffe)

Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Methoden zur Förderung von Kompetenzen für eine demokratische Kultur - Schriftliche Reflexionen von Lehramtsstudierenden aus bildungswissenschaftlichen Seminaren - Wehde, Janis; Bloh, Bea

Wie war das damals? Oral history und Zeitzeug:innenbefragung - Diederich, Julia ((Über-)Leben im Nationalsozialismus)

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (Physical Review B)

“I do not know! but why?” — Local model-agnostic example-based explanations of reject - Artelt, André; Visser, Roel; Hammer, Barbara (Neurocomputing)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Warum es ein Marketing für die Berufsbildung braucht – Zwei Fallstudien über die Verbesserung der Durchlässigkeit durch innovative Fortbildungen auf der DQR-Stufe 5 - Peitz, Nina-Madeleine; Müller-Wegner, Max; Ertl, Hubert
Mittels Fallstudien zweier Projekte des bundesweiten Programms InnoVET (Zukunft gestalten – Innovationen für eine exzellente berufliche Bildung) wird untersucht, wie innovative Aufstiegsfortbildungen auf der DQR-Stufe 5 zu einer durchlässigeren Berufsbildung im Verbund gestaltet und Ergebnisse transferiert werden. Zwecks nachhaltiger Implementation am Markt wird der Bedarf eines Marketings deutlich.

Segment-Less Continuous Speech Separation of Meetings: Training and Evaluation Criteria - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Continuous Speech Separation (CSS) has been proposed to address speech overlaps during the analysis of realistic meeting-like conversations by eliminating any overlaps before further processing. CSS separates a recording of arbitrarily many speakers into a small number of overlap-free output channels, where each output channel may contain speech of multiple speakers. This is often done by applying a conventional separation model trained with Utterance-level Permutation Invariant Training (uPIT), which exclusively maps a speaker to an output channel, in sliding window approach called stitching. Recently, we introduced an alternative training scheme called Graph-PIT that teaches the separation network to directly produce output streams in the required format without stitching. It can handle an arbitrary number of speakers as long as never more of them overlap at the same time than the separator has output channels. In this contribution, we further investigate the Graph-PIT training scheme. We show in extended experiments that models trained with Graph-PIT also work in challenging reverberant conditions. Models trained in this way are able to perform segment-less CSS, i.e., without stitching, and achieve comparable and often better separation quality than the conventional CSS with uPIT and stitching. We simplify the training schedule for Graph-PIT with the recently proposed Source Aggregated Signal-to-Distortion Ratio (SA-SDR) loss. It eliminates unfavorable properties of the previously used A-SDR loss and thus enables training with Graph-PIT from scratch. Graph-PIT training relaxes the constraints w.r.t. the allowed numbers of speakers and speaking patterns which allows using a larger variety of training data. Furthermore, we introduce novel signal-level evaluation metrics for meeting scenarios, namely the source-aggregated scale- and convolution-invariant Signal-to-Distortion Ratio (SA-SI-SDR and SA-CI-SDR), which are generalizations of the commonly used SDR-based metrics for the CSS case.
Keywords: Continuous Speech Separation; Source Separation; Graph-PIT; Dynamic Programming; Permutation Invariant Training

On Word Error Rate Definitions and Their Efficient Computation for Multi-Speaker Speech Recognition Systems - von Neumann, Thilo; Boeddeker, Christoph; Kinoshita, Keisuke; Delcroix, Marc; Haeb-Umbach, Reinhold (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
We propose a general framework to compute the word error rate (WER) of ASR systems that process recordings containing multiple speakers at their input and that produce multiple output word sequences (MIMO). Such ASR systems are typically required, e.g., for meeting transcription. We provide an efficient implementation based on a dynamic programming search in a multi-dimensional Levenshtein distance tensor under the constraint that a reference utterance must be matched consistently with one hypothesis output. This also results in an efficient implementation of the ORC WER which previously suffered from exponential complexity. We give an overview of commonly used WER definitions for multi-speaker scenarios and show that they are specializations of the above MIMO WER tuned to particular application scenarios. We conclude with a discussion of the pros and cons of the various WER definitions and a recommendation when to use which.
Keywords: Word Error Rate; Meeting Recognition; Levenshtein Distance

MeetEval: A Toolkit for Computation of Word Error Rates for Meeting Transcription Systems - von Neumann, Thilo; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (Proc. CHiME 2023 Workshop on Speech Processing in Everyday Environments)
MeetEval is an open-source toolkit to evaluate all kinds of meeting transcription systems. It provides a unified interface for the computation of commonly used Word Error Rates (WERs), specifically cpWER, ORC WER and MIMO WER along other WER definitions. We extend the cpWER computation by a temporal constraint to ensure that only words are identified as correct when the temporal alignment is plausible. This leads to a better quality of the matching of the hypothesis string to the reference string that more closely resembles the actual transcription quality, and a system is penalized if it provides poor time annotations. Since word-level timing information is often not available, we present a way to approximate exact word-level timings from segment-level timings (e.g., a sentence) and show that the approximation leads to a similar WER as a matching with exact word-level annotations. At the same time, the time constraint leads to a speedup of the matching algorithm, which outweighs the additional overhead caused by processing the time stamps.
Keywords: Speech Recognition; Word Error Rate; Meeting Transcription

Schnittstelle zwischen Programmen und Forschung – Die Forschungsbegleitung InnoVET - Ertl, Hubert; Peitz, Nina-Madeleine (Datenreport zum Berufsbildungsbericht 2023. Informationen und Analysen zur Entwicklung der beruflichen Bildung)

Berufliche Fortbildung – gleichwertige Alternativen zum Hochschulabschluss. Erste Erkenntnisse aus dem Innovationswettbewerb InnoVET - Bednarz, Sigrid; Martens, Stephanie; Peitz, Nina-Madeleine (Berufsbildung in Wissenschaft und Praxis)

Komponierte Ambiguität. Ein anderer Blick auf polyphone Messen des 15. und 16. Jahrhunderts - Höink, Dominik (Kirchenmusikalisches Jahrbuch)

A Memetic NSGA-II for the Multi-Objective Flexible Job Shop Scheduling Problem with Real-time Energy Tariffs - Burmeister, Sascha Christian; Guericke, Daniela; Schryen, Guido (Flexible Services and Manufacturing Journal)

‘I had a patient who…’: Narratives of Vicarious Experience in GPs’ Discourse on Domestic Violence - Mildorf, Jarmila (Narrative Structure and Narrative Knowing in Medicine and Science)

Class Expression Learning with Multiple Representations - Ngonga Ngomo, Axel-Cyrille; Demir, Caglar; Kouagou, N'Dah Jean; Heindorf, Stefan; Karalis, Nikoloas; Bigerl, Alexander (Compendium of Neurosymbolic Artificial Intelligence)

Anmerkungen zum Begriff des digitalen Kapitalismus. - Christian, Fuchs (Theorien des digitalen Kapitalismus)

Spatial Diarization for Meeting Transcription with Ad-Hoc Acoustic Sensor Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Proc. Asilomar Conference on Signals, Systems, and Computers)
We propose a diarization system, that estimates “who spoke when” based on spatial information, to be used as a front-end of a meeting transcription system running on the signals gathered from an acoustic sensor network (ASN). Although the spatial distribution of the microphones is advantageous, exploiting the spatial diversity for diarization and signal enhancement is challenging, because the microphones’ positions are typically unknown, and the recorded signals are initially unsynchronized in general. Here, we approach these issues by first blindly synchronizing the signals and then estimating time differences of arrival (TDOAs). The TDOA information is exploited to estimate the speakers’ activity, even in the presence of multiple speakers being simultaneously active. This speaker activity information serves as a guide for a spatial mixture model, on which basis the individual speaker’s signals are extracted via beamforming. Finally, the extracted signals are forwarded to a speech recognizer. Additionally, a novel initialization scheme for spatial mixture models based on the TDOA estimates is proposed. Experiments conducted on real recordings from the LibriWASN data set have shown that our proposed system is advantageous compared to a system using a spatial mixture model, which does not make use of external diarization information.
Keywords: Diarization; time difference of arrival; ad-hoc acoustic sensor network; meeting transcription

Additive Manufacturing and Mechanical Properties of Auxetic and Non-Auxetic Ti24Nb4Zr8Sn Biomedical Stents: A Combined Experimental and Computational Modelling Approach - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
The effect of plaque deposition (atherosclerosis) on blood flow behaviour is investigated via computational fluid dynamics and structural mechanics simulations. To mitigate the narrowing of coronary artery atherosclerosis (stenosis), the computational modelling of auxetic and non-auxetic stents was performed in this study to minimise or even avoid these deposition agents in the future. Computational modelling was performed in unrestricted (open) conditions and restricted (in an artery) conditions. Finally, stent designs were produced by additive manufacturing, and mechanical testing of the stents was undertaken. Auxetic stent 1 and auxetic stent 2 exhibit very little foreshortening and radial recoil in unrestricted deployment conditions compared to non-auxetic stent 3. However, stent 2 shows structural instability (strut failure) during unrestricted deployment conditions. For the restricted deployment condition, stent 1 shows a higher radial recoil compared to stent 3. In the tensile test simulations, short elongation for stent 1 due to strut failure is demonstrated, whereas no structural instability is noticed for stent 2 and stent 3 until 0.5 (mm/mm) strain. The as-built samples show a significant thickening of the struts of the stents resulting in short elongations during tensile testing compared to the simulations (stent 2 and stent 3). A modelling framework for the stent deployment system that enables the selection of appropriate stent designs before in vivo testing is required. This leads to the acceleration of the development process and a reduction in time, resulting in less material wastage. The modelling framework shall be useful for doctors designing patient-specific stents.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Post-Processing Independent Evaluation of Sound Event Detection Systems - Ebbers, Janek; Haeb-Umbach, Reinhold; Serizel, Romain (Proceedings of the 8th Detection and Classification of Acoustic Scenes and Events 2023 Workshop (DCASE2023))
Due to the high variation in the application requirements of sound event detection (SED) systems, it is not sufficient to evaluate systems only in a single operating mode. Therefore, the community recently adopted the polyphonic sound detection score (PSDS) as an evaluation metric, which is the normalized area under the PSD receiver operating characteristic (PSD-ROC). It summarizes the system performance over a range of operating modes resulting from varying the decision threshold that is used to translate the system output scores into a binary detection output. Hence, it provides a more complete picture of the overall system behavior and is less biased by specific threshold tuning. However, besides the decision threshold there is also the post-processing that can be changed to enter another operating mode. In this paper we propose the post-processing independent PSDS (piPSDS) as a generalization of the PSDS. Here, the post-processing independent PSD-ROC includes operating points from varying post-processings with varying decision thresholds. Thus, it summarizes even more operating modes of an SED system and allows for system comparison without the need of implementing a post-processing and without a bias due to different post-processings. While piPSDS can in principle combine different types of post-processing, we here, as a first step, present median filter independent PSDS (miPSDS) results for this year’s DCASE Challenge Task4a systems. Source code is publicly available in our sed_scores_eval package (https://github.com/fgnt/sed_scores_eval).

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, D.; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

"Would You Give the Same Priority to the Bank and a Game? I Do Not!" Exploring Credential Management Strategies and Obstacles during Password Manager Setup - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Acar, Yasemin; Fahl, Sascha (Nineteenth Symposium on Usable Privacy and Security, SOUPS 2023, Anaheim, CA, USA, August 5-7, 2023)

"I wouldn’t want my unsafe code to run my pacemaker": An Interview Study on the Use, Comprehension, and Perceived Risks of Unsafe Rust - Höltervennhoff, Sandra; Klostermeyer, Philip; Wöhler, Noah; Acar, Yasemin; Fahl, Sascha (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

Ethical Frameworks and Computer Security Trolley Problems: Foundations for Conversations - Kohno, Tadayoshi; Acar, Yasemin; Loh, Wulf (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

Who Comes Up with this Stuff? Interviewing Authors to Understand How They Produce Security Advice - Neil, Lorenzo; Sri Ramulu, Harshini; Acar, Yasemin; Reaves, Bradley (Nineteenth Symposium on Usable Privacy and Security, SOUPS 2023, Anaheim, CA, USA, August 5-7, 2023)

Beyond the Boolean: How Programmers Ask About, Use, and Discuss Gender - Bouma-Sims, Elijah; Acar, Yasemin (Proc. ACM Hum. Comput. Interact.)

Beyond the Boolean: How Programmers Ask About, Use, and Discuss Gender - Bouma-Sims, Elijah; Acar, Yasemin (CoRR)

"Make Them Change it Every Week!": A Qualitative Exploration of Online Developer Advice on Usable and Secure Authentication - Klemmer, Jan H.; Gutfleisch, Marco; Stransky, Christian; Acar, Yasemin; Sasse, M. Angela; Fahl, Sascha (CoRR)

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

Kant and the Role(s) of Doctrines of Methods (Journal of Transcendental Philosophy)

Your Smartphone Is Watching You - Eine technikkritische Untersuchung der menschlichen Freiheit und Antiquiertheit im Zeitalter der Digitaltechnologie - Mac Award, Daria-Leona

Im Dialog: Theologische Grundlagen und religionsdidaktische Impulse für die Praxis des kokoRUs. Rezension zu Bernd Schröder/Jan Woppowa (Hg.): Theologie für den konfessionell-kooperativen Religionsunterricht. Ein Handbuch, Tübingen 2021 - Neumann, Anna (Praktische Theologie. Zeitschrift für Praxis in Kirche, Gesellschaft und Kultur)